Respostas

2013-12-08T13:44:07-02:00
d1=x²+y²+6x-4y+12=0 

centro:

6/-2 = -3
-4/-2 = 2

raio: (-3)² + 2² - r² = 12
9 + 4 -r² = 12
13 -r² = 12
-r² = 12-13
-r² = -1 .(-1)
r² = 1
r = 1

Centro (-3,2) raio: 1


d2= x²+y²+6x-4y+4=0

centro:
6/-2 = -3
-4/-2 = 2

raio:

(-3)² + 2² -r² = 4
9 + 4 - r² = 4
13 -r² = 4
-r² = 4-13
-r² = -9 .(-1)
r = 3

Centro(-3,2) raio: 3

Distância entre os centros:

(-3,2) e (-3,2)

(-3+3)² + (2-2)² =
9 -18 + 9 +4 -8 + 4 = 
18 -18 + 8 -8 = 
0
Comentário foi eliminado
=D pode ?
Comentário foi eliminado
Comentário foi eliminado
ok